2018
DOI: 10.1007/s00404-018-4750-4
|View full text |Cite
|
Sign up to set email alerts
|

Can ebselen prevent cisplatin-induced ovarian damage?

Abstract: Our results from using an experimental rat model of CP chemotherapy suggest that ebselen use may ameliorate ovarian damage by preventing oxidative injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…A recent report indicated that cisplatin therapy leads to the dilatation, vacuolization, and loss of tubular epithelial cells; and glomerular degeneration and edema in the kidney tissues, as seen in our study (Eren et al, 2018). The previous findings and our results also confirmed that cisplatin produces high H score in the kidney (Ozkok and Edelstein, 2014;Eren et al, 2018;Soyman et al, 2018;). In the literature, these histopathological findings point out the nephrotoxicity (Yao et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A recent report indicated that cisplatin therapy leads to the dilatation, vacuolization, and loss of tubular epithelial cells; and glomerular degeneration and edema in the kidney tissues, as seen in our study (Eren et al, 2018). The previous findings and our results also confirmed that cisplatin produces high H score in the kidney (Ozkok and Edelstein, 2014;Eren et al, 2018;Soyman et al, 2018;). In the literature, these histopathological findings point out the nephrotoxicity (Yao et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…The underlying mechanisms of tubular cell death due to cisplatin treatment includes oxidative stress, DNA adducts, inflammation, mitochondrial dysfunction, apoptosis, and direct cytotoxicity (Yao et al, 2007). However, several studies showed the protective effects of antioxidative molecules against cisplatin-induced damages (Eren et al, 2018;Haghi-Aminjan et al, 2018;Soyman et al, 2018). Therefore, we may suggest that squalene treatment ameliorated the cisplatin-induced histopathological damages in the kidney tissue by regulating the balance of the redox system due to its antioxidative effect (Ondrejková et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They investigated ovarian injury by examining follicles histochemically and evaluated the immunoreactive intensity of AMH in ovarian tissue 16 . Soyman et al reported that antioxidant ebselen prevents cisplatin‐induced ovarian damage 39 . They found high Cu/Zn‐SOD and GSH levels, low malonyldialdehyde (MDA) and NOx levels, and high‐serum AMH hormone levels in the ovarian tissue of ebselen treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ebselen ameliorates ovarian damage by reducing oxidative stress caused by cisplatin (Ref. 37). The administration of ebselen can induce apoptosis in multiple myeloma (MM) cell lines by enhancing the production of endogenous ROS (Ref.…”
Section: Involvement In Diseasementioning
confidence: 99%
“…Based on extensive research, several potential clinical applications of ebselen in the treatment of different diseases have been reported in cell lines studies (Refs 20, 21, 27, 33), animal experiments (Refs 28, 34, 35, 36, 37) and clinical trials (Refs 38, 39, 40, 41). In mammalian cells, ebselen works as a GPx-like compound and peroxiredoxin mimic through Trx and TrxR to scavenge hydrogen peroxide and peroxynitrite (Ref.…”
Section: Introductionmentioning
confidence: 99%